Influenza A virus shedding and reinfection during the post-weaning period in swine: longitudinal study of two nurseries - Storms, Suzanna M.; Leonardi-Cattolica, Antonio; Prezioso, Tara; Varga, Csaba; Wang, Leyi; Lowe, James (Frontiers in Veterinary Science, 2024)
IntroductionInfluenza A virus in swine (IAV-S) is common in the United States commercial swine population and has the potential for zoonotic transmission.ObjectiveTo elucidate influenza shedding the domestic pig population, we evaluated two commercial swine farms in Illinois, United States, for 7 weeks. Farm 1 had a recent IAV-S outbreak. Farm 2 has had IAV-S circulating for several years.MethodsForty post-weaning pigs on Farm 1 and 51 pigs from Farm 2 were individually monitored and sampled by nasal swabs for 7 weeks.ResultsRT-PCR results over time showed most piglets shed in the first 2 weeks post weaning, with 91.2% shedding in week one, and 36.3% in week two. No difference in the number of pigs shedding was found between the two nurseries. Reinfection events did differ between the farms, with 30% of piglets on Farm 1 becoming reinfected, compared to 7.8% on Farm 2. In addition, whole genome sequencing of nasal swab samples from each farm showed identical viruses circulating between the initial infection and the reinfection periods. Sequencing also allowed for nucleic and amino acid mutation analysis in the circulating viruses, as well the identification of a potential reverse zoonosis event. We saw antigenic site mutations arising in some pigs and MxA resistance genes in almost all samples.ConclusionThis study provided information on IAV-S circulation in nurseries to aid producers and veterinarians to screen appropriately for IAV-S, determine the duration of IAV-S shedding, and predict the occurrence of reinfection in the nursery period.